Narcissism, the Experience of Pain, and Risky Decision Making - Buelow, Melissa T.; Brunell, Amy B. (Frontiers in Psychology, 2020)
Personality characteristics and situational factors are known to influence performance on behavioral decision making tasks; however, variability exists in the relationship between narcissism and decision making. In addition, recent research suggests that the presence of acute pain can negatively affect decisions, and even the threat of pain can also cause changes in decision making. Narcissists are known to experience social pain differently than non-narcissists, but relatively little is known about how physical pain is experienced. The present study examined the influence of both pain and narcissism on risky decision making task performance. Participants (n=248) completed assessments of the narcissistic admiration and rivalry concept as well as vulnerable narcissism. They were asked to complete a pain recall task before administration of the Balloon Analogue Risk Task (BART), Columbia Card Task (CCT), Game of Dice Task (GDT), and Iowa Gambling Task (IGT). Although individuals who recalled a socially painful experience took less risks on the IGT across trials, no effect of narcissism was seen on any of the tasks. Recalling a physically or socially painful situation did not negatively affect decision making on the BART, CCT, or GDT. Results are discussed in the context of previous research on narcissism, pain, and cognitive task performance.